2001
DOI: 10.4049/jimmunol.166.7.4380
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Killer Cell Ig-Like Receptors of Rhesus Monkeys

Abstract: Because the killer cell Ig-like receptors (KIRs) have only been characterized in humans and chimpanzees, we do not have a full understanding of their evolutionary history. Therefore, cDNAs encoding the KIR molecules of five rhesus monkeys were characterized, and were found to differ from the KIR molecules identified in humans and chimpanzees. Whereas only one KIR2DL4 molecule is detected in humans and chimpanzees, two distinct KIR2DL4 homologues were identified in the monkeys. Although the two human KIR3DL mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
169
1
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(185 citation statements)
references
References 38 publications
10
169
1
5
Order By: Relevance
“…Contrary to rodent models, outbred nonhuman primate colonies show similar levels of natural diversity in many of their immune-related genes, as is encountered in the human population. There are hints that this may also apply to the KIR gene system [33,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrary to rodent models, outbred nonhuman primate colonies show similar levels of natural diversity in many of their immune-related genes, as is encountered in the human population. There are hints that this may also apply to the KIR gene system [33,36].…”
Section: Discussionmentioning
confidence: 99%
“…Where the group B haplotypes are characterized by the presence of one or more of the following genes -KIR2DL5, KIR2DS1, KIR2DS2, KIR2DS3, KIR2DS5, and KIR3DS1 -the group A haplotypes are defined by the absence of these genes. Moreover, much of the observed haplotype diversity can be explained by dividing these haplotype groups into centromeric and telomeric parts, whereby new haplotypes may be formed by equal and unequal crossover events between these regions [32].With regard to the rhesus macaque, only a few individual animals have been analyzed for their KIR content, since the fulllength KIR transcripts of some unrelated animals have been sequenced [33,34]. The subsequent analyses showed that the KIR system in this macaque species is polygenic and polymorphic, and can encode inhibitory and activating molecules with three extracellular domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 2DL4 is highly conserved not only in pygmy chimpanzee (Bonobo) (44), but also in rhesus monkey (Macaca mulatta) (45), suggesting that 2DL4 serves an important role in primates. Important insights regarding the functions of 2DL4 have emerged from several recent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Mm-KIR2DL4 is the only ortholog of a human KIR among rhesus monkey KIR (32). Whereas Mm-KIR2DL4 encodes a full-length protein with two ITIM motifs, the orthologs in apes and humans all exhibit degradation either in one or other ITIM motif (chimpanzee and human) or change in the position of translational termination (orangutan and certain human alleles; Fig.…”
Section: Discussionmentioning
confidence: 99%